Steel: A new round of protectionism in American trade - Christian A. Conrad (Intereconomics, 1995)
Traditionally the American steel industry is the most protected industrial sector in the USA and internationally it is the largest user of anti-dumping and anti-subsidy proceedings. At the end of 1994 a ruling from the GATT Panel settled the most recent trade dispute in the steel market. A number of the anti-dumping and anti-subsidy proceedings applied for by US integrated steel producers in 1992 remain in effect. The following paper outlines the latest trade dispute in the steel trade, beginning with an overview of the various rounds of protectionism to date, and seeks to analyse the background to and causes of the dispute.
Keywords: 330